Klasifikasi Ilmu Pengetahuan Dalam Perspektif Jābir Bin Ḥayyān - Asep N. Musadad (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
Abstract : The central purpose of this article is to provide a preliminary exploration on epistemological background of the classical Islamic sciences through the investigation on the classification of knowledge. One of the earliest exponent to turn to this problem is Jābir bin Ḥayyān (Geber) (721 - 815 AD), known as the Father of Arabic and – indirectly – Latin Alchemy. Start on describing  Jābir’s  profile  and  his  significance  in  Islamic  philosophy,  this  article  discusses the  classification  of  knowledge  according  to  him  in  his  book  “Kitāb  al-Ḥudūd”  (Book  of Limits), in which he make his own classification of various knowledge. It finally deals with the philosophical basis of the classification and the intellectual perspective of its author.